2011
DOI: 10.1093/aje/kwr111
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Relative Risk of Mortality for Singles: Meta-Analysis and Meta-Regression

Abstract: Never-married persons (singles) constitute a growing demographic group; yet, the magnitude of the all-cause relative mortality risk for nonelderly singles is not known and important moderating factors have not been explored. The authors used meta-analysis to examine 641 risk estimates from 95 publications that provided data on more than 500 million persons. The comparison group consisted of currently married individuals. The mean hazard ratio for mortality was 1.24 (95% confidence interval: 1.19, 1.30) among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 63 publications
1
33
1
4
Order By: Relevance
“…The excess mortality of the never-married increased markedly compared with that of the married among both sexes. (This result is in contrast to the meta-analysis carried out by Roelfs et al (2011), which showed that the mortality gap between the married and the never-married widened most strongly among women.) In fact, mortality was almost constant, or even increasing, among the nevermarried in the first part of the study period, while in more recent years it has declined among all groups of the nonmarried -although not as sharply as among the married.…”
Section: The Increasing Mortality Advantage Of the Marriedcontrasting
confidence: 95%
“…The excess mortality of the never-married increased markedly compared with that of the married among both sexes. (This result is in contrast to the meta-analysis carried out by Roelfs et al (2011), which showed that the mortality gap between the married and the never-married widened most strongly among women.) In fact, mortality was almost constant, or even increasing, among the nevermarried in the first part of the study period, while in more recent years it has declined among all groups of the nonmarried -although not as sharply as among the married.…”
Section: The Increasing Mortality Advantage Of the Marriedcontrasting
confidence: 95%
“…It is not obvious how this could affect mortality, though. Effects of individual marital status were as expected (Roelfs et al, 2011;Shor et al, 2012). Only a few studies have estimated effects of the family structure in the community on health, health behaviour or mortality (Kravdal, 2007;Thorlindson et al, 2012), or considered the importance of family structure as a conditioning variable (Burrows et al, 2011;Huijts and Kraaykamp, 2011;Subramanian et al, 2008).…”
Section: A Few Comments On the Effects Of Individual And Aggregate Somentioning
confidence: 58%
“…parish, municipality, county) where mortality is high and another person who is representative of a low-mortality area may differ by socio-economic resources, values, marital status or other individual characteristics with a bearing on mortality (e.g. Elo, 2009;Roelfs et al, 2011;Shor et al, 2012;Waite and Lehrer, 2003). If this were the only reason for geographical mortality variation, the variation could in theory be reduced by, for example, stimulating a number of people with low education in the most disadvantaged areas to improve their formal qualifications or providing income support.…”
Section: Effects Of Own Characteristicsmentioning
confidence: 99%
“…As in the general population [1415], the risk of death among survivors was associated with black race, absence of a spouse/partner, <high school education, and annual household income <$20,000. We observed for the first time that mortality risk increases with the annual frequency of physician visits; the greater the severity of chronic conditions, the greater the frequency of physician visits.…”
Section: Discussionmentioning
confidence: 98%